Ur III texts in the Schøyen collection - Dahl, Jacob L. (CUSAS: Cornell University Studies in Assyriology and Sumerology, 2020)
Intro -- Title Page -- Copyright Page -- Contents -- Statement of Provenance -- Series Editor's Preface -- Preface -- Conventions -- Abbreviations -- Catalog -- Concordances -- 1. Introduction -- 2. Archival Documents -- Archival Tags -- Sealed Tags with Inscriptions -- Other Sealed Tags -- Commodity Tags -- 3. Timekeeping -- 4. Accounts -- Short Accounts -- Structure of the Neo-Sumerian Account -- "Debits" (sag-nig2-gur11-ra-kam) -- "Credits" (ša3-bi-ta zi-ga-am3) -- Operating Balance -- Colophon -- 5. Equivalencies -- 6. Accountability -- 7. Receipts: The Primary Documents -- Sealed Receipts -- Receipts Mentioning a Conveyor (giri3) -- Unsealed Receipts -- Sealed Receipts with kišib3 PN -- Receipts with Envelopes -- Unsealed Receipts -- Receipt Copies -- mu-kux(DU) Documents -- ba-zi and zi-ga Documents -- i3-dab5 Documents -- in-la2 Documents -- 8. Administration of Work -- Inventories -- Smaller Inventories -- "Work-Crew Lists" -- Receipts -- Accounts -- Miscellaneous Work Texts -- 9. Letters -- 10. Messenger Texts -- Type I Messenger Texts -- Type Isub Messenger Texts -- Type II Messenger Texts -- Type III Messenger Texts -- Type IV Messenger Texts -- 11. Legal Texts -- Purchase Documents -- Loan Documents -- Miscellaneous Legal Documents -- 12. Miscellaneous Texts -- An Inventory of Date Palms -- An Inventory of Fallen Cattle -- An Inventory of the Treasury of Alim-maḫ -- An Exercise Tablet? -- The Volume of Ditches and Canals -- A Field Plan Without a Drawing -- Bundles of Reed for the Storehouse of the Edana -- Two Exercises in Cereal Computations -- A Discarded Exercise Tablet? -- Animals for Gods -- A Receipt Without Context -- A Receipt of Three Receipts? -- Two Inventories of Unknown Purpose -- Two Fragments Glued Together -- Offerings from the Governor -- Not a Tag? -- Two Notes or Exercise Tablets?.